National surveillance of 2, 3, 7, 8-substituted polychlorinated dibenzo-p-dioxins/furans in soil in Taiwan. (July 2018) - Hsu, Yi-Chyun; Que, Danielle E.; Gou, Yan-You; Tsou, Tsui-Chun; Liu, Chung-Kun; Wang, Yen-Ling; Hou, Wen-Che; Lin, Yi-Hsien; Liu, Wen-Yao; Chao, How-Ran; Lee, Wen-Jhy
Abstract: In this study, the polychlorinated dibenzo-p-dioxin/furan (PCDD/F) levels in 381 soil samples coming from different background areas (n = 238) and contaminated areas (n = 143) in Taiwan were investigated from 2011 to 2015 using high resolution gas chromatograph/high resolution mass spectrometry (HRGC/HRMS). The contaminated areas showed higher PCDD/F contamination as compared to the background areas (1230 vs 749 pg/g dry weight (dw)); 14.0 vs 6.25 pg WHO2005 -TEQ/g dw). The lowest levels were recorded in the outlying islands (1.28 pg WHO2005 -TEQ/g dw). PCDD/F congener distribution profiles in the background and contaminated areas as well as on the islands varied. OCDD was the dominant congener in almost all locations, including the northern background (87.7%) and central contaminated (74.2%) areas. Other dominant species included OCDF and 1, 2, 3, 4, 6, 7, 8-HpCDD. Levels of PCDD/F-TEQs in Taiwanese soils, including the background areas, were higher than in some developing countries and regions with global background levels due to high industrialization except for the contaminated areas. Geographic differences in dioxin-contaminated soils were also shown in this study. Higher soil dioxin-TEQs were observed in locations with high populations and population densities. Despite the limitations, the economic status of Taiwan represented by the annual averaged family income (AAFI) was positively correlated to soil dioxin-TEQs. Highlights: High soil dioxins were found in the background and contaminated areas in Taiwan. Low soil dioxins in outlying islands are from low activity of human and industry. Soil dioxin distribution is different between background and contaminated areas. Population and population densities are positively correlated with soil dioxins. Economic activity is probably correlated with dioxin contamination in soils.